Nickel‐Catalyzed Enantioselective Reductive Alkyl‐Carbamoylation of Internal Alkenes. (25th July 2022) - Wu, Xianqing; Turlik, Aneta; Luan, Baixue; He, Feng; Qu, Jingping; Houk, K. N.; Chen, Yifeng
Abstract: Herein, we leverage the Ni‐catalyzed enantioselective reductive dicarbofunctionalization of internal alkenes with alkyl iodides to enable the synthesis of chiral pyrrolidinones bearing vicinal stereogenic centers. The application of newly developed 1‐Nap Quinim is critical for formation of two contiguous stereocenters in high yield, enantioselectivity, and diastereoselectivity. This catalytic system also improves both the yield and enantioselectivity in the synthesis of α, α‐dialkylated γ‐lactams. Computational studies reveal that the enantiodetermining step proceeds with a carbamoyl‐Ni I intermediate that is reduced by the Mn reductant prior to intramolecular migratory insertion. The presence of the t ‐butyl group of the Quinim ligand leads to an unfavorable distortion of the substrate in the TS that leads to the minor enantiomer. Calculations also support an improvement in enantioselectivity with 1‐Nap Quinim compared to p ‐tol Quinim. Abstract : The enantioselective reductive dicarbofunctionalization of internal alkenes has been developed to enable the formation of vicinal stereogenic centers. This protocol allows for facile synthesis of chiral pyrrolidinones bearing vicinal or quaternary stereocenters with excellent enantio‐ and diastereoselectivities. DFT calculations suggest that the enantiodetermining step is intramolecular migratory insertion with a carbamoyl‐Ni I intermediate.